2020
DOI: 10.1007/s00464-020-07819-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel self-assembling peptide to prevent hemorrhage after EMR, a feasibility and safety study

Abstract: Background A novel self-assembling peptide (SAP) can be applied to the post-endoscopic mucosal resection (EMR) defect to treat oozing bleedings. It has been suggested to stimulate early healing of damaged vessels. We hypothesized that SAP application could prevent delayed bleeding (DB) after EMR and performed a prospective cohort study to determine feasibility and safety. Methods A total of 48 consecutive patients who underwent EMR between June 2018 and August 2019 for large lesions in the esophagus, duodenum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Previous reports have described clinical experiences using PuraStat® (3-D Matrix Europe, Caluire et Cuire, France), a novel hydrogel composed of a synthetic hemostatic material and administered in a prefilled syringe. Soons et al showed in a single-arm study that prophylactic PuraStat application after endoscopic mucosal resection is safe and can be performed within a few minutes; however, the postoperative bleeding rate was not different from that reported with existing methods 20 . In a randomized controlled trial, Subramaniam et al showed that PuraStat is an effective hemostat that can reduce the need for heat therapy to treat bleeding during ESD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous reports have described clinical experiences using PuraStat® (3-D Matrix Europe, Caluire et Cuire, France), a novel hydrogel composed of a synthetic hemostatic material and administered in a prefilled syringe. Soons et al showed in a single-arm study that prophylactic PuraStat application after endoscopic mucosal resection is safe and can be performed within a few minutes; however, the postoperative bleeding rate was not different from that reported with existing methods 20 . In a randomized controlled trial, Subramaniam et al showed that PuraStat is an effective hemostat that can reduce the need for heat therapy to treat bleeding during ESD.…”
Section: Discussionmentioning
confidence: 91%
“…This may be because the hydrogel flows off the bottom of the ulcer before robust gelation. It has also been reported that the position of the ulcer can affect appropriate gelation 20 . These factors could be relevant because the previously reported hydrogels were composed of a single agent, which makes controlling their physical properties difficult.…”
Section: Discussionmentioning
confidence: 99%
“…A very low delayed bleeding rate was found (3%) and the bleeding activity was stopped within 70 s [ 9 ]. The application of PuraStat after EMR is feasible and safe which could be shown in 48 patients [ 20 ]. The most recent RCT of 101 patients comparing PuraStat to cautery reported a haemostatic efficacy rate of 92.6% for intra procedural oozing bleeds encountered during oesophageal or colonic ESD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…RADA16, the only commercial agent in use, is a transparent, synthetic, self-assembling peptide hemostatic gel that works by forming a hydrogel matrix scaffold on the tissue surface. The rate of delayed bleeding after RADA16 ranged from 0% to 11% in 3 studies (61–63).…”
Section: Prophylactic Measuresmentioning
confidence: 99%